Performance of a Monarch Butterfly for Various Flapping Angle - ., Aaroh; Zuber, Mohammad; Md Abdul Khader, Shah; Kalburgi, Sagar; Illyani Basri, Ernnie; Arifin Ahmad, Kamarul (International Journal of Engineering and Technology, 2018)
The butterfly is an insect highly evolved to perform various flight regimes. From gliding flight to manoeuvers involving spontaneous changes in direction, the butterfly is considered a marvel of aerodynamic evolution. Recent demand in the development of micro-aerial vehicles (MAVs) has led scientists to study these creatures in greater depth to get a better understanding of the lift generating mechanisms adopted by them. This study focuses on the evaluation of gliding performance of the Monarch butterfly. A CAD model of a Monarch butterfly wing is modelled using CATIA, taking into account only a single wing of wingspan 53.381 mm which is used to simulate the gliding motion of the butterfly. The gliding performance analysis suggests that a maximum aerodynamic coefficient of 3.597 is achieved for the current wing orientation at 8Â° AoA.Â Â